Impact of Arsenic Stress on the Antioxidant System and Photosystem of Arthrospira platensis - Jiawei Liu; Jie Du; Di Wu; Xiang Ji; Xiujuan Zhao (Biology, 2024)
Arthrospira platensis exhibits high tolerance to arsenic; however, the mechanisms underlying its response to the arsenic stress have not been fully elucidated. This study investigated the growth and resistance mechanisms of A. platensis under As3+ stress by measuring physiological and biochemical indices, conducting transcriptome sequencing, and validating the results through qPCR. The findings show that arsenic stress affected the antioxidant system and photosynthetic pigment synthesis in A. platensis. The algae mitigated arsenic-induced oxidative stress by increasing cellular metabolic rates, enhancing cell wall stability, and reducing membrane lipid peroxidation. Transcriptome analysis revealed that pathways related to oxidative phosphorylation and chlorophyll degradation were upregulated under arsenic stress, while the expression of membrane transporters was significantly downregulated. Additionally, the algae alleviated arsenic stress by producing hydrogen and polyamine compounds. This study provides insights into the mechanisms of A. platensis response to arsenic stress and elucidates the molecular pathways involved in the stress response to As3+.